Pengaruh Kualitas Layanan, Kepercayaan, Dan Kepuasan Terhadap Loyalitas Nasabah : Studi Kasus Bank Sumut Syariah KCP Lubuk Pakam - Dui April Yani Simangunsong; Annio Indah Lestari Nasution; Muhammad Lathief Ilhamy Nasution (Journal of Islamic Economics and Finance, 2023)
Dui April Yani Simangunsong’s research (2023) Thesis entitled "The Influence of Service Quality, Trust, and Satisfaction on Customer Loyalty (Case Study of Bank Sumut Syariah Kcp Lubuk Pakam)" with thesis supervisor 1 Mrs. Annio Indah Lestari, M,Si and supervisor 2 Mr. Muhammad Lathief Ilhamy Nasution, M.E.I This research aims to examine the influence of service quality, trust and satisfaction on customer loyalty (case study of Bank Sumut Syariah Kcp Lubuk Pakam) both partially and simultaneously. The type of research used is quantitative research with questionnaire data collection techniques with Likert scale measurements. The subjects used in this research were customers who saved at the North Sumatra Sharia Bank as many as 100 respondents and were taken using sampling techniques. Data analysis techniques using Spss statistics 25. The results of this research show that: first, Service Quality has a positive and significant effect on Customer Loyalty, with a value of tcount > ttable (9.575 > 1.661) and a significant value of 0.042 < 0.05. Second, Trust has a positive and significant effect on Customer Loyalty with a value of tcount > ttable (8.748 > 1.661) and a significant value of 0.026 < 0.005. Third, satisfaction has a positive and significant effect on customer loyalty with a value of tcount > ttable (7.300 > 1.661) and a significant value of 0.037 < 0.005. Fourth, Service Quality, Trust and Satisfaction, on Customer Loyalty with a value of Fcount > Ftable (37.449 > 2.47) and a significant value of 0.000 < 0.005.